Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)
\(\Rightarrow x\left(x-5\right)=0\)
\(\Rightarrow\left[\begin{array}{nghiempt}x=0\\x-5=0\end{array}\right.\)
\(\Rightarrow\left[\begin{array}{nghiempt}x=0\\x=5\end{array}\right.\)
b)
\(\Rightarrow3x\left(x-2\right)-2\left(x-2\right)=0\)
\(\Rightarrow\left(x-2\right)\left(3x-2\right)=0\)
\(\Rightarrow\left[\begin{array}{nghiempt}x-2=0\\3x-2=0\end{array}\right.\)\(\Rightarrow\left[\begin{array}{nghiempt}x=2\\x=\frac{2}{3}\end{array}\right.\)
c)
\(\Rightarrow\left(3x-1\right)\left(5x+x-2\right)=0\)
\(\Rightarrow\left(3x-2\right)^2.2=0\)
\(\Rightarrow3x-2=0\)
\(\Rightarrow x=\frac{2}{3}\)
\(x\left(3x-5\right)=0\)
\(\Rightarrow\hept{\begin{cases}x=0\\3x-5=0\end{cases}\Rightarrow\hept{\begin{cases}x=0\\x=\frac{5}{3}\end{cases}}}\)
Vậy \(x\in\left\{0;\frac{5}{3}\right\}\)
a) \(x\left(3x-5\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=0\\3x-5=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=0\\x=\frac{5}{3}\end{cases}}}\)
b) \(3x^2-27=0\)
\(\Leftrightarrow3x^2=27\)
\(\Leftrightarrow x^2=9\)
\(\Leftrightarrow x=\pm3\)
c) \(\left(x-5\right)^2=x-5\)
\(\Leftrightarrow x^2-10x+25-x+5=0\)
\(\Leftrightarrow x^2-11x+30=0\)
\(\Leftrightarrow\left(x-6\right)\left(x-5\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x-6=0\\x-5=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=6\\x=5\end{cases}}}\)
d) \(2\left(x+7\right)-x^2-7x=0\)
\(\Leftrightarrow2x+14-x^2-7x=0\)
\(\Leftrightarrow-x^2-5x+14=0\)
\(\Leftrightarrow\left(x-7\right)\left(x-2\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x-7=0\\x-2=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=7\\x=2\end{cases}}}\)
e)\(7x\left(x-3\right)+2.3x=0\)
\(\Leftrightarrow7x^2-21x+6x=0\)
\(\Leftrightarrow7x^2-15x=0\)
\(\Leftrightarrow x\left(7x-15\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=0\\7x-15=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=0\\x=\frac{15}{7}\end{cases}}}\)
#H
a)\(3x\left(x-2\right)+2\left(2-x\right)=0\)
\(\Leftrightarrow3x\left(x-2\right)-2\left(x-2\right)=0\)
\(\Leftrightarrow\left(3x-2\right)\left(x-2\right)=0\)
\(\Rightarrow\orbr{\begin{cases}3x-2=0\\x-2=0\end{cases}}\)\(\Rightarrow\orbr{\begin{cases}x=\frac{2}{3}\\x=2\end{cases}}\)
b)\(5x\left(3x-1\right)+x\left(3x-1\right)-2\left(3x-1\right)=0\)
\(\Leftrightarrow\left(3x-1\right)\left(5x+x-2\right)=0\)
\(\Leftrightarrow\left(3x-1\right)\left(6x-2\right)=0\)
\(\Leftrightarrow2\left(3x-1\right)\left(3x-1\right)=0\)
\(\Leftrightarrow\left(3x-1\right)^2=0\Rightarrow3x-1=0\Rightarrow x=\frac{1}{3}\)
a/3x(x-2)+2(2-x)=0
=>(2-3x)(2-x)=0
=>\(\orbr{\begin{cases}2-3x=0\\2-x=0\end{cases}}\)=>\(\orbr{\begin{cases}3x=2\\x=2\end{cases}}\)=>\(\orbr{\begin{cases}x=\frac{2}{3}\\x=2\end{cases}}\)
b/5x(3x-1)+x(3x-1)-2(3x-1)=0
=>(5x+x-2)(3x-1)=0
=>(6x-2)(3x-1)=0
=>\(\orbr{\begin{cases}6x-2=0\\3x-1=0\end{cases}}\)=>\(\orbr{\begin{cases}6x=2\\3x=1\end{cases}}\)=>x=\(\frac{1}{3}\)
a) 3x(x-1)+x-1=0
<=>3x(x-1)+(x-1)=0
<=>(x-1)(3x+1)=0
<=>x-1=0 hoặc 3x+1=0
<=>x=1 hoặc 3x=-1
<=>x=1 hoặc x=-1/3
b)2(x+3)-x^2 - 3x = 0
<=>2(x+3)-x(x+3)=0
<=>(x+3)(2-x)=0
<=>x+3=0 hoặc 2-x=0
<=>x=-3 hoặc x=2
(Ko chép lại đề)
\(a.\Rightarrow\orbr{\begin{cases}3x+5=0\\4-3x=0\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=-\frac{5}{3}\\x=\frac{4}{3}\end{cases}}\)
\(b.\left(3x-2\right)\left(x-7\right)=0\)
\(\Rightarrow\orbr{\begin{cases}3x-2=0\\x-7=0\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=\frac{2}{3}\\x=7\end{cases}}\)
\(c.7x^2=28\)
\(x^2=4\)
\(x^2=2^2\)
\(x=\pm2\)
\(d.\left(2x+1\right)\left(1+x\right)=0\)
\(\Rightarrow\orbr{\begin{cases}2x+1=0\\1+x=0\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=-\frac{1}{2}\\x=-1\end{cases}}\)
a)\(\left(3x+5\right)\left(4-3x\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}3x+5=0\\4-3x=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=-\frac{5}{3}\\x=\frac{4}{3}\end{cases}}}\)
b)\(3x\left(x-7\right)-2\left(x-7\right)=0\)
\(\Leftrightarrow\left(x-7\right)\left(3x-2\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x-7=0\\3x-2=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=7\\x=\frac{2}{3}\end{cases}}}\)
c) \(7x^2-28=0\)
\(\Leftrightarrow7x^2=28\)
\(\Leftrightarrow7x^2=7.4\)
\(\Leftrightarrow x^2=4\)
\(\Leftrightarrow x=\pm2\)
d)\(\left(2x+1\right)+x\left(2x+1\right)=0\)
\(\Leftrightarrow\left(2x+1\right)\left(1+x\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}2x+1=0\\1+x=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=-\frac{1}{2}\\x=-1\end{cases}}}\)
#H
a) \(x^3+3x^2+3x+2=0\)
<=> \(x^3+x^2+x+2x^2+2x+2=0\)
<=> \(x\left(x^2+x+1\right)+2\left(x^2+x+1\right)=0\)
<=> \(\left(x+2\right)\left(x^2+x+1\right)=0\)
tự làm
b) \(x^4-2x^3+2x-1=0\)
<=> \(\left(x^4-3x^3+3x^2-x\right)+\left(x^3-3x^2+3x-1\right)=0\)
<=> \(x\left(x^3-3x^2+3x-1\right)+\left(x^3-3x^2+3x-1\right)=0\)
<=> \(\left(x^3-3x^2+3x-1\right)\left(x+1\right)=0\)
<=> \(\left(x-1\right)^3\left(x+1\right)=0\)
tự làm
c) \(x^4-3x^3-6x^2+8x=0\)
<=> \(x\left(x^3-3x^2-6x+8\right)=0\)
<=> \(x\left[\left(x^3+x^2-2x\right)-\left(4x^2+4x-8\right)\right]=0\)
<=>\(x\left[x\left(x^2+x-2\right)-4\left(x^2+x-2\right)\right]=0\)
<=> \(x\left(x-4\right)\left(x^2+x-2\right)=0\)
<=> \(x\left(x-4\right)\left(x-1\right)\left(x+2\right)=0\)
tự làm
a) => (x-1) (3x +1) =0 =>
x-1 =0 => x =1
hoặc 3x +1 =0 => x =-1/3
b) =>2(x+3) - x(x+3) =0 => (x+3)(2-x) =0
x +3 =0 => x = -3
hoặc 2-x =0 => x =2
\(a)\) \(\left(5x-1\right)^2-5x\left(5x-1\right)=0\)
\(\Leftrightarrow\)\(\left(5x-1\right)\left(5x-1-5x\right)=0\)
\(\Leftrightarrow\)\(\left(5x-1\right).\left(-1\right)=0\)
\(\Leftrightarrow\)\(5x-1=0\)
\(\Leftrightarrow\)\(5x=1\)
\(\Leftrightarrow\)\(x=\frac{1}{5}\)
Vậy \(x=\frac{1}{5}\)
\(b)\) \(x\left(x+1\right)\left(x+2\right)=0\)
Suy ra \(x=0\) hoặc \(x+1=0\) hoặc \(x+2=0\)
\(\Leftrightarrow\)\(x=0\) hoặc \(x=-1\) hoặc \(x=-2\)
Vậy \(x=0\) hoặc \(x=-1\) hoặc \(x=-2\)
\(c)\) \(\left(3x+2\right)x-3\left(3x+2\right)=0\)
\(\Leftrightarrow\)\(\left(3x+2\right)\left(x-3\right)=0\)
\(\Leftrightarrow\)\(\orbr{\begin{cases}3x+2=0\\x-3=0\end{cases}\Leftrightarrow\orbr{\begin{cases}3x=0-2\\x=0+3\end{cases}}}\)
\(\Leftrightarrow\)\(\orbr{\begin{cases}3x=-2\\x=3\end{cases}\Leftrightarrow\orbr{\begin{cases}x=\frac{-2}{3}\\x=3\end{cases}}}\)
Vậy \(x=\frac{-2}{3}\) hoặc \(x=3\)
Chúc bạn học tốt ~
a/ \(\left(5x-1\right)^2-5x\left(5x-1\right)=0\)
<=> \(\left(5x-1\right)\left(5x-1-5x\right)=0\)
<=> \(-1\left(5x-1\right)=0\)
<=> \(5x-1=0\)
<=> \(5x=1\)
<=> \(x=\frac{1}{5}\)
b/ \(x\left(x+1\right)\left(x+2\right)=0\)
<=> \(x=0\) hoặc \(\orbr{\begin{cases}x+1=0\\x+2=0\end{cases}}\)
<=> \(x=0\)hoặc \(\orbr{\begin{cases}x=-1\\x=-2\end{cases}}\)
c/ \(\left(3x+2\right)x-3\left(3x+2\right)=0\)
<=> \(\left(3x+2\right)\left(x-3\right)=0\)
<=> \(\orbr{\begin{cases}3x+2=0\\x-3=0\end{cases}}\)
<=> \(\orbr{\begin{cases}3x=-2\\x=3\end{cases}}\)
<=> \(\orbr{\begin{cases}x=-\frac{2}{3}\\x=3\end{cases}}\)
\(x\left(3x-5\right)-9x+15=0\)
\(\Leftrightarrow x\left(3x-5\right)-3\left(3x-5\right)=0\)
\(\Leftrightarrow\left(x-3\right)\left(3x-5\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x-3=0\\3x-5=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=3\\x=\frac{5}{3}\end{cases}}\)
\(3x\left(x-5\right)-2\left(5-x\right)=0\)
\(\Leftrightarrow3x\left(x-5\right)+2\left(x-5\right)=0\)
\(\Leftrightarrow\left(3x+2\right)\left(x-5\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}3x+2=0\\x-5=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=\frac{-2}{3}\\x=5\end{cases}}\)
x^2-3x=0
\(\Leftrightarrow\)x(x-3)=0
\(\Leftrightarrow\)X=0 hay x-3=0
\(\Leftrightarrow\)x=0 hay x=3
\(x^2-3x=0\)
\(x\left(x-3\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x=0\\x-3=0\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=0\\x=3\end{cases}}\)